Primary Students' Attitudes towards Peers with Disabilities in Physical Education in Saudi Arabia - Majed M. Alhumaid (MDPI AG, 2023)
The attitudes of students without disabilities toward their peers with disabilities are considered an important determinant of successful inclusion in physical education settings. Nonetheless, there is limited research on this topic in non-Western societies, especially in Arab contexts. Thus, to address this paucity in the literature, this study aimed to assess the general attitudes of Saudi students without disabilities towards their peers with disabilities and examine the associations between selected student-related variables (e.g., gender, age, type of school, school location, having a family member or a friend or a classmate with a disability, and having experience of playing with a person with a disability) and attitudes of students without disabilities. A total of 972 students aged 9-12 years old (Mage = 10.6; SD = 1.1; girls = 49.7%) completed the Arabic version of the Scale of Attitudes toward Students with Disabilities in Physical Education-Primary Education (SASDPE-PE). Data analysis indicated that, in general, participants reported positive attitudes toward their peers with disabilities in physical education classes. Despite boys being more likely to hold positive attitudes than girls, no significant difference between them existed. The results showed that 10-year-old participants reported more significantly positive attitudes than those in the other age groups. Participants attending public schools reported more significant positive attitudes toward their peers with disabilities in physical education classes compared to those attending private schools. Having a friend with a disability was linked to students without disabilities having positive attitudes towards their peers with disabilities. In contrast, having a family member or a classmate with disabilities and having played with a person with a disability were not related to such positive attitudes. The current study's findings have significant implications for inclusive educational practices.